Internet, nueva herramientas para jóvenes periodistas del cantón Babahoyo del año 2018 - Guerrero Plaza, Guisell Alejandra (2019)
The present work entitled: INTERNET, NEW TOOL FOR YOUNG JOURNALISTS OF THE BABAHOYO CANTON OF THE YEAR 2018, aimed to determine the incidence of the use of the Internet as a tool for young journalists of the Babahoyo canton of the year 2018. For this, field methodologies were used, inductive, deductive and analytical - synthetic, from which the mechanisms to develop it were established. In that sense, a population of 290 young professionals between the ages of 21 and 35 years of age was used, selecting a sample of 168 journalists to whom a questionnaire was applied with the request to obtain the relevant information to plant the respective conclusions . Among the main results found, 98% of them were determined that the internet is an important tool for the exercise of the profession. In that sense it is established that it must comply with ethical and social responsibility. On the other hand, it was determined that 80% of young people have a third level degree in the area of Social Communication, and only 20% of them have postgraduate training. Finally, it is important to note that 17% of professionals are unemployed and 57% of the total sample is working and that 27% are not associated with any company but exercise freely. In conclusion of this work it was possible to determine what satisfaction of the reader depends a lot on the ethical, innovative and creative quality that the communicator has to present the information through any of the platforms offered by the internet